anonymous
  • anonymous
Find the zeros of f(x) = -x^2 + 4x - 3 by using a table and a graph. Enter the missing numeral of the answer 1, ___. Use a number only. Find the zeros of the function f(x) = x^2 - 5x - 6 by factoring. What is the largest zero of the function? Enter a number only. Find the zeros of the function g(x) = x^2 - 8x by factoring. What is the smallest zero of the function? Enter a number only. Find the zeros of the function h(x) = x^2 +4x by factoring. What is the smallest zero of the function? Enter a number only. Find the zeros of the function f(x) = x^2 - 7x + 6 by factoring. What is the largest zero of the function? Enter a number only. Find the zeros of the function g(x) = x^2- 6x - 16 by factoring. What is the largest zero of the function? Enter a number only.
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
For the first part you have to plug in 1 for x and calculate the corresponding y value -(1)^2+4(1)-3=y=0 For the second part the factor is (x-6)(x+1)=0 so x=6,-1 (6 is the larger of these values) For the third part the factor is (x-8)(x+0)=0 so x=8,0 (0 is the smaller of these values) For the fourth part the factor is (x+4)(x+0)=0 so x=-4,0 (-4 is the smaller of these values) For the fifth part the factor is (x-1)(x-6)=0 so x=1,6 (6 is the larger of these values) For the sixth part the factor is (x-8)(x+2)=0 so x=8,-2 (8 is the larger of these values) You can check my factoring my multiplying each out and seeing if you get the original equation
anonymous
  • anonymous
thanks

Looking for something else?

Not the answer you are looking for? Search for more explanations.